Analisis Kelayakan Investasi Keuangan Haji dalam Pembiayaan Infrastruktur dan Tingkat Imbal Hasil Badan Pengelola Keuangan Haji (Bpkh) - Beny Witjaksono (Faculty of Economics and Business Universitas Jenderal Soedirman, 2020)
This paper analyzes the investment portfolio of hajj funds in infrastructure financing and the level of returns managed by the Hajj Financial Management Board (BPKH). This research was conducted through case studies and literature studies to obtain secondary data. Data collected were analyzed quantitatively and qualitatively descriptive. The results showed that the feasibility of investment in hajj funds in infrastructure financing is feasible in sharia perspective. Under Law 34/2014, Hajj financial investments are aimed at obtaining optimal value benefits for improving the service of Hajj implementation by prioritizing aspects of the safety/integrity of the funds of prospective pilgrims.